The feasibility and potential effectiveness of a conventional and exergame intervention to alter balance-related outcomes including fall risk: a mixed methods study - Rogers, Christine (Department of Health and Rehabilitation Sciences, 2021)
Introduction: Fall risk, occurrence and injury is increasing as the world ages, and Africa and other emerging regions will not be spared. Similarly, the rise of noncommunicable diseases, compressed morbidity and lack of physical activity present major challenges. This novel feasibility study explored the use of an exergaming technology compared with a conventional, evidence-based exercise programme (Otago Exercise Programme) to reduce fall risk by improving balance, and to inform a large-scale randomised control trial. Methodology: Mixed methods study in independent older adults with established fall risk. The quantitative component employed feasibility RCT methodology. Cluster randomisation assigned interventions to sites. Single blinding was used. Both interventions were offered for six months. A variety of balance-related endpoints (e.g., Timed Up and Go, Dynamic Gait Index, Mini-BESTest) were used to find the most applicable. Patient-centred variables included questionnaires regarding depression, physical activity levels, quality of life and estimates of self-efficacy for exercise. Qualitative focus groups explored participants' experiences of falls and the exergaming intervention using a phenomenology lens. Results: Site and participant recruitment was simple and readily achievable, with low numbers need to screen required. Eligibility criteria were confirmed and more added. Adherence and attrition were major challenges. Cluster randomisation appeared to exacerbate between-group differences at baseline. The exergaming intervention produced preliminary evidence in its favour, with results approaching Minimal Clinically Important Difference compared with the evidence-based intervention. The experience of the exergaming intervention was regarded as positive by focus group participants. Barriers and facilitators are reported. Discussion: Methodological issues in the literature have prevented firm consensus on the use of exergaming in falls prevention, although studies are abundant. The current study used rigorous methodology in the novel context of a developing region, which offers numerous challenges for older adults. Implications for a large-scale, fully funded RCT are discussed. Lessons learned can be used to scale up service delivery for an under-served population; and promote the aim of well-being for all at all ages.